2020
DOI: 10.5433/1679-0359.2020v41n6supl2p2937
|View full text |Cite
|
Sign up to set email alerts
|

Co-inoculation of Bradyrhizobium japonicum and Azospirillum brasilense on the physiological quality of soybean seeds

Abstract: The success of the soybean crop depends on the physiological quality of seeds, which can be favored by beneficial microorganisms, however, it may be impaired by unfavorable environmental conditions. The aim of this study was to evaluate the effect of co-inoculation with Bradyrhizobium japonicum and Azospirillum brasilense on the physiological quality of soybean seeds obtained in the 2017/2018 crop season, from a field trial involving 23 cultivars submitted to co-inoculation (in-furrow) or without coinoculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In the joint analysis of the total number of nodules per plant, the treatments with 200 mL ha -1 (seed or in-furrow) and 300 mL ha -1 applied in-furrow did not differ statistically from each other but surpassed the treatment with 100 mL 50 kg -1 seed with both the standard and the mixed inoculants (Table 4). These results corroborate the reports of Groppa et al (1998) and Libório et al (2020) that point out favorable influences of A. brasilense on soybean nodules.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In the joint analysis of the total number of nodules per plant, the treatments with 200 mL ha -1 (seed or in-furrow) and 300 mL ha -1 applied in-furrow did not differ statistically from each other but surpassed the treatment with 100 mL 50 kg -1 seed with both the standard and the mixed inoculants (Table 4). These results corroborate the reports of Groppa et al (1998) and Libório et al (2020) that point out favorable influences of A. brasilense on soybean nodules.…”
Section: Resultssupporting
confidence: 92%
“…N fertilization reduced the dry nodule mass in the Colina-SP and Selvíria-MS areas, which was expected due to the contribution of mineral N. In Maringá-PR, the lowest mass of nodules per plant was observed in control (without inoculant and mineral N) due to the lower number of nodules in these plants. A study of in-furrow co-inoculation with several soybean cultivars revealed an increased number of nodules from 36.9 in control to 44.4 nodules per plant on average with the co-inoculation (Libório et al, 2020). In general, the supply of 200 kg ha -1 of mineral N showed inferior results regarding the number and mass of nodules (Table 4).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation